3D structure elucidation of thermostable L2 lipase from thermophilic Bacillus sp. L2 - Raja Abdul Rahman, Raja Noor Zaliha; Mohd Shariff, Fairolniza; Basri, Mahiran; Salleh, Abu Bakar (MDPI, 2012)
The crystallization of proteins makes it possible to determine their structure by X-ray crystallography, and is therefore important for the analysis of protein structure-function relationships. L2 lipase was crystallized by using the J-tube counter diffusion method. A crystallization consisting of 20% PEG 6000, 50 mM MES pH 6.5 and 50 mM NaCl was found to be the best condition to produce crystals with good shape and size (0.5 × 0.1 × 0.2 mm). The protein concentration used for the crystallization was 3 mg/mL. L2 lipase crystal has two crystal forms, Shape 1 and Shape 2. Shape 2 L2 lipase crystal was diffracted at 1.5 Å and the crystal belongs to the orthorhombic space group P212121, with unit-cell parameters a = 72.0, b = 81.8, c = 83.4 Å, α = β = γ = 90°. There is one molecule per asymmetric unit and the solvent content of the crystals is 56.9%, with a Matthew’s coefficient of 2.85 Å Da−1. The 3D structure of L2 lipase revealed topological organization of α/β-hydrolase fold consisting of 11 β-strands and 13 α-helices. Ser-113, His-358 and Asp-317 were assigned as catalytic triad residues. One Ca2+ and one Zn2+ were found in the L2 lipase molecule.